2014
DOI: 10.1016/j.devcel.2014.07.015
|View full text |Cite|
|
Sign up to set email alerts
|

Protocadherin-17 Mediates Collective Axon Extension by Recruiting Actin Regulator Complexes to Interaxonal Contacts

Abstract: In the process of neuronal wiring, axons derived from the same functional group typically extend together, resulting in fascicle formation. How these axons communicate with one another remains largely unknown. Here, we show that protocadherin-17 (Pcdh17) supports this group extension by recruiting actin polymerization regulators to interaxonal contact sites. Pcdh17 is expressed by a subset of amygdala neurons, and it accumulates at axon-axon boundaries because of homophilic binding. Pcdh17 knockout in mice sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
108
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(113 citation statements)
references
References 38 publications
4
108
1
Order By: Relevance
“…Another report has shown that Pcdh17 knockout in mice results in defects in the extension of axons from specific subdivisions of the amygdala, a center in the brain that regulates emotions and motivation (Hayashi et al, 2014). This phenotype has been confirmed through observations of impaired axon growth from amygdala fragments that had been explanted in vitro, supporting the idea that Pcdh17 mediates axon growth.…”
Section: Role Of D2-protocadherins In Axon Growth and Patterningsupporting
confidence: 56%
See 4 more Smart Citations
“…Another report has shown that Pcdh17 knockout in mice results in defects in the extension of axons from specific subdivisions of the amygdala, a center in the brain that regulates emotions and motivation (Hayashi et al, 2014). This phenotype has been confirmed through observations of impaired axon growth from amygdala fragments that had been explanted in vitro, supporting the idea that Pcdh17 mediates axon growth.…”
Section: Role Of D2-protocadherins In Axon Growth and Patterningsupporting
confidence: 56%
“…Similar to the classic cadherins, d2-protocadherins accumulate at cell-cell contact sites through homophilic interactions (Hayashi et al, 2014;Hirano et al, 1999;Nakao et al, 2008;Tai et al, 2010). So far, it appears that trans-interactions occur only between the same subtypes (Hoshina et al, 2013;Tai et al, 2010) (S.H., unpublished data).…”
Section: D2-protocadherins Modulate Classic-cadherin-mediated Cellcelmentioning
confidence: 99%
See 3 more Smart Citations